308 nm UV excimer light in monotherapy or combined to topical khellin 4% and/or tacrolimus 0.1% in the treatment of vitiligo. (2015) - Nistico, Steven; Cannarozzo, Giovanni; Sannino, Mario; Duca, Ester del
No abstract available